Why work "at home"? Oxfam's value-added and the UK Poverty Programme. Issue 4 (19th May 2019) - Pickering-Saqqa, Susannah
ABSTRACT: International development NGOs are in existential crisis. Their legitimacy and added value are increasingly challenged. While scholars have focused on legitimacy, work on "value-added" is scarce. In particular, no research addresses the value of domestic programmes to international NGOs. This article rectifies this, focusing on the case of Oxfam GB's UK Poverty Programme (UKPP). Using empirical research from 35 interviews with Oxfam GB staff, partners and beneficiaries and over 150 archive documents, the article identifies seven assets through which the programme provides value added to Oxfam GB. It highlights the possibility that these could offer insights into the dimensions of future INGOs.